A Beveridge curve decomposition for Austria: What drives the unemployment rate? - Michael Christl (Agenda Austria, 2019)
The Austrian Beveridge curve shifted in 2014, leading to ongoing academic discussions about the reasons behind this shift. While some have argued that the shift was caused by a supply shock due to labour market liberalization, others have stated that matching efficiency decreased. Using a new decomposition method, combined with detailed labour market flow data, we are the first to disentangle supply-side, demand-side and matching factors, which could potentially cause a shift in the Beveridge curve in Austria. We find empirical evidence to confirm that the increase in the unemployment rate in Austria after 2011 can indeed be attributed to a supply-side shock. But, contrary to other research, our analysis shows that the shift in the Beveridge curve after 2014 was mainly caused by a decrease in matching efficiency, indicating a rising mismatch problem in the Austrian labour market.
Keywords: J62; J63; E24; E32; 330; Beveridge curve; crisis; mismatch; unemployment; structural unemployment; vacancies